2023
DOI: 10.1186/s12864-023-09119-5
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering key genomic regions controlling flag leaf size in wheat via integration of meta-QTL and in silico transcriptome assessment

Abstract: Background Grain yield is a complex and polygenic trait influenced by the photosynthetic source-sink relationship in wheat. The top three leaves, especially the flag leaf, are considered the major sources of photo-assimilates accumulated in the grain. Determination of significant genomic regions and candidate genes affecting flag leaf size can be used in breeding for grain yield improvement. Results With the final purpose of understanding key genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…Cultivars from Central and Northern Europe showed higher values for FLW and FLA compared to North American and Eastern Europe-Western Asia accessions. Extensive phenotypic variation among these traits has been widely reported mainly in DH and RIL populations 16 , 22 and diverse panels 17 , 30 , however, an association on the genotype´s origin as described here has not been previously documented. Future studies should assess if differences in FL dimensions are related to an indirect selection effect concerning the photosynthetic active radiation available at different latitudes.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Cultivars from Central and Northern Europe showed higher values for FLW and FLA compared to North American and Eastern Europe-Western Asia accessions. Extensive phenotypic variation among these traits has been widely reported mainly in DH and RIL populations 16 , 22 and diverse panels 17 , 30 , however, an association on the genotype´s origin as described here has not been previously documented. Future studies should assess if differences in FL dimensions are related to an indirect selection effect concerning the photosynthetic active radiation available at different latitudes.…”
Section: Discussionmentioning
confidence: 57%
“…As previously reported, flag leaf morphological traits are quantitative traits controlled by multiple genes 6 , 65 . Recently some authors have compiled previous reports related to QTL involved in flag morphological traits on different wheat chromosomes 22 , 65 . Even though previous efforts mainly using RILs and DH population have documented markers linked with flag leaf morphology on 1A 22 , 1B 19 , 36 , 2A, 19 , 2B 19 , 3A 36 , 3B 22 , 4A 22 , 4B 22 , 5A 19 , 36 , 5B 19 , 6B 36 , 7A 22 , 7B and 7D 36 , those QTNs documented in this work have not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the availability of molecular markers and genetic maps, numerous quantitative trait loci (QTLs) related to flag leaf-related traits have been discovered in rice, barley and wheat [ 19 22 ]. In rice, Chen et al reported a flag width QTL, qFLW4 , which contains a narrow NAL1 gene with a 74.8 kb interval [ 23 ].…”
Section: Introductionmentioning
confidence: 99%